Which statement is true about this equation? 3(-y + 7) = 3(y + 5) + 6
A. The equation has one solution, y=0
B. The equation has one solution, y=-1
C. The equation has no solution.
D. the equation has infinitely many solutions.

Respuesta :

Answer:

A

Step-by-step explanation:

the equation has only one solution

Answer:

A. The equation has one solution, y=0

Step-by-step explanation:

use the answers to get the answers

3(-y + 7) = 3(y + 5) + 6

-3y + 21 = 3y + 15 + 6

21 -15 -6 = 6y

0 = 6y

y = 0